Ancient Mesopotamia - Dalal, Anita (Redding, Conn. Brown Bear Books, 2009)
Introduction -- Timelines -- Early peoples -- Sites : Shanidar -- The first farmers -- Builders and traders -- First civilization -- Sites : Tell Madhhur -- Birth of the city -- Sites : Uruk -- States in conflict -- Sites : Nippur, Ebla -- Sites : Ur -- Kings of Agade -- Rival kingdoms -- Law and society -- Mittani and the Assyrians -- The Kassites -- New powers -- Israel and Judah -- Sites : Kalhu -- Assyria triumphant -- Sites : Ashur, Nineveh -- Babylonian revival -- Sites : Babylon -- The Persian Empire -- Darius' empire -- Sites : Susa -- The final years
Includes index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Iraq -- Civilization -- To 634